2011
DOI: 10.1103/physreve.84.021127
|View full text |Cite
|
Sign up to set email alerts
|

Current reversals in a rocking ratchet: The frequency domain

Abstract: Motivated by recent work [D. Cubero et al., Phys. Rev. E 82, 041116 (2010)], we examine the mechanisms which determine current reversals in rocking ratchets as observed when varying the frequency of the drive. We found that a class of these current reversals in the frequency domain is precisely determined by dissipation-induced symmetry breaking. Our experimental and theoretical work thus extends and generalizes the previously identified relationship between dynamical and symmetry-breaking mechanisms in the ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In Fig. 14 we show the results of numerical integration of equations (86,87). By applying operationsŜ r and θ → θ + π, one can see that J(θ + π) = −J(θ), which allows for the inversion of the current direction by shifting θ, see Fig.…”
Section: Applications: Numerical Studiesmentioning
confidence: 99%
“…In Fig. 14 we show the results of numerical integration of equations (86,87). By applying operationsŜ r and θ → θ + π, one can see that J(θ + π) = −J(θ), which allows for the inversion of the current direction by shifting θ, see Fig.…”
Section: Applications: Numerical Studiesmentioning
confidence: 99%
“…with φ 1 = φ 2 = π/2. Previous work for one-dimensional systems has shown that the biharmonic driving, breaking all the system symmetries, is able to produce a current, whose amplitude and direction can be controlled via the amplitude and the frequency of the strength of the driving [4][5][6][7][8][9][10]. In the absence of coupling between transverse degrees of freedom, ac driving of the form of Eq.…”
Section: Model and Definitionsmentioning
confidence: 99%
“…Other groups have pointed out the role of symmetry in current reversal [21,29,30]. However, its role is fundamentally different: asymmetry determines the direction of the transport.…”
Section: Introductionmentioning
confidence: 99%